2018
DOI: 10.18517/ijaseit.8.1.2699
|View full text |Cite
|
Sign up to set email alerts
|

Design of e-Teaching Portfolio System Framework for e-Tutor Competency Management

Abstract: In e-learning, tutors support learners through their understanding of e-learning environments as well as their knowledge of the subjects under their charge, and also play the role of preventing the dropout of learners. Therefore, measures to manage efficient competency of tutors are necessary. Whereas e-portfolios are made from the viewpoint of learner's learning, e-teaching portfolios are made from the viewpoint of the activities of teachers including tutors. Although there have been discussions about the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…For example, Cukurbasi and Kiyici (2018) found that the pre-service teachers who took their opinions thought that e-portfolio activities in Facebook environment contributed to improve their performance, had a practical and useful system and allowed them to do group work. Again, different researchers (Baris & Tosun, 2013;Barrot, 2016;Haave, 2016;Kim & Kim, 2018;Ozgur, 2016;Venville, Cleak & Bould, 2017;Woo et. al., 2014) reached the conclusions that the participants had positive attitudes in e-portfolio activities in Facebook environment.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cukurbasi and Kiyici (2018) found that the pre-service teachers who took their opinions thought that e-portfolio activities in Facebook environment contributed to improve their performance, had a practical and useful system and allowed them to do group work. Again, different researchers (Baris & Tosun, 2013;Barrot, 2016;Haave, 2016;Kim & Kim, 2018;Ozgur, 2016;Venville, Cleak & Bould, 2017;Woo et. al., 2014) reached the conclusions that the participants had positive attitudes in e-portfolio activities in Facebook environment.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Different researchers in the literature (Ada et. al., 2016;Baris & Tosun, 2013;Haave, 2016;Kim & Kim, 2018;Venville, Cleak & Bould, 2017;Woo et. al., 2014) have revealed the positive effects of e-portfolio studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several questions emerge based on this review of literature. First, a more complete picture of servant leader development is to be had (Eva et al, 2019; Kim et al, 2014). Research is required for organizations who hope to accelerate the development within their ranks.…”
Section: Opportunities For Future Researchmentioning
confidence: 99%
“…The uses of web 2.0 features in the learning context is driven by user participation. This ecosystem has been described as Learning 2.0 (Inamorato dos Santos & Punie, 2016; Kim & Kim, 2016). Davis (2005) states that the concept of Web 2.0 is related with attitude and not only the technology because it directs back to an original web, but user participation is encouraged and make a social network.…”
Section: Persuasive Systemmentioning
confidence: 99%